Validating Pharma Machinery: A Journey To Find a Line Somewhere Above Baseline with Science and Risk Consideration for Cost Efficient Facility Requirement - Pitoyo Amrih (Mesin, 2018)
Every industries should be aware about how their product quality are build. It began with the end in mind about a detail specification of the product, a quality atribut designed to the product profile, process and technology choice. Then it will initiate a requirement of the facility for those need. Pharmaceutical product is one in many manufacturing industries that need to be carefully manage in term of product quality and the consideration that it can be harm to the consumer. The impact can also come from a requirement specification of its facility1. To protect the drugs consumer, we can use the term 'patient safety' then, authority made a regulation that became a coridor to lead the industry on how the good manufacturing pratices should be conducted. Regulator put it in the terminology: GMP (Good Manufacturing Practices). But they give only general statement about what a 'good manufacturing' is. Most of the time it needs detail technical explanation. Especially for the engineers perspective.  Some pharmaceutical engineering professional organization try to describe the minimum requirement should be designed for pharmaceutical facility purpose. A Baseline. But the baseline sometimes is not a clear bold line, Most of the time, in very detail technical decision, it can be a wide grey area. How high we put our requirement level above baseline corelate with how expensive the cost will be.